Effects of Social Media Use on Psychological Well-Being: A Mediated Model - Ostic, Dragana; Qalati, Sikandar Ali; Barbosa, Belem; Shah, Syed Mir Muhammad; Galvan Vela, Esthela; Herzallah, Ahmed Muhammad; Liu, Feng (Frontiers in Psychology, 2021)
The growth in social media use has given rise to concerns about the impacts it may have on users’ psychological well-being. This paper’s main objective is to shed light on the effect of social media use on psychological well-being. Building on contributions from various fields in the literature, it provides a more comprehensive study of the phenomenon by considering a set of mediators, including social capital types (i.e. bonding social capital and bridging social capital), social isolation, and smartphone addiction. The paper includes a quantitative study of 940 social media users from Mexico, using structural equation modeling to test the proposed hypotheses. The findings point to an overall positive indirect impact of social media usage on psychological well-being, mainly due to the positive effect of bonding and bridging social capital. The empirical model’s explanatory power is 45.1%. This paper provides empirical evidence and robust statistical analysis that demonstrates both positive and negative effects coexist, helping to reconcile the inconsistencies found so far in the literature.